Optimization of diagnostics and treatment of posttraumatic onycholysis - M. S. Neznakhina; G. A. Petrova; O. YE. Garanina; I. L. Shlivko; D. O. Ellinsky; K. S. Petrova (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
Onycholysis is a peculiar and prevalent nail affection conditioned by the detachment of the distal part of the nail from the nail bed. The absence of any reliable diagnostics criteria often results in diagnostics errors, inadequate treatment and reduced patient's life quality. Goal of the research. To find out whether it is possible to use OCT for diagnosing onycholysis and Merz Spezial Dragees for the treatment of posttraumatic onycholysis, and to reasonably confirm the drug efficacy using OCT. Materials and methods. The study involved 15 volunteers with posttraumatic onycholysis aged 20-35 (mean age: 28) including 12 female and 3 male subjects. One nail was affected in 7 cases, and two nails were affected in 8 cases. The area of the onycholysis zone was less than one third of the nail area (mean NAPSI value: 2.9 points). For the purposes of clinical control over the efficacy of Merz Spezial Dragees and nail monitoring, the OCT method was applied. Tests were performed 5 and 7 weeks after the observation and treatment onset. Results. Merz Spezial Dragees contribute to faster regression of clinical manifestations of posttraumatic onycholysis and recovery of the normal state of the nail.